FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN ALAT KONTRASEPSI TUBEKTOMI PADA PASANGAN USIA SUBUR DI RUMAH SAKIT UMUM SAWERIGADING KOTA PALOPO - Hardianto Dg. Salimung (JURNAL FENOMENA KESEHATAN, 2019)
Background: The family planning program is an integral part of the national development program and aims to create economic, spiritual and socio-cultural welfare for the Indonesian population so that it can be achieved. Objective: To determine the Factors That Influence To The Selection Of Method On Tubectomy Contraception in Fertile Age Couples In Sawerigading Hospital In Palopo City Method: This type of research used in this study is an analytical survey using a case control approach where researchers study the factors associated with the selection of tubectomy contraceptives by collecting data by looking at past events to determine whether there are risk factors experienced. The population in this study were all family planning acceptors who came to visit the KIA room at the Sawerigading Palopo Hospital. The number of cases was 33 people and control 66 people so the total sample was 99 people. Data were processed using Statistical Product and Service Solution (SPSS) and analyzed univariately and bivariately with a chi-square static test and presented in the form of a frequency distribution table. Results: age relationship (P-value = 0.000), education (P value = 0.774), parity obtained (P value = 0.001), and mother's knowledge (P value = 0.024) Conclusion: There is a relationship between age, education, parity and knowledge of mothers with the selection of contraceptive tools for tubectomies in infertile women in Sawerigading Palopo Hospital.